On the evaluation of the performance of SMEs from a human and organisational capital perspective. (10th May 2010) - Leitao, Joao; Franco, Mario
This article makes a contribution to the eclectic framework of entrepreneurship through the evaluation of the impact of human and organisational capital, determined by the entrepreneur on the performance of Small- and Medium-sized Enterprises (SMEs). The use of a stepwise procedure provides the selection of significant variables that have an impact on the performance of SMEs. When only non-economic indicators are considered for measuring performance, regarding human capital, we find that the only significant variable is enthusiasm at work. In relation to organisational capital, the significant variables are an efficient organisational structure, participative management, incentives for interdisciplinary discussion and dialogue and frequent meetings of working groups. In turn, when economic indicators are considered, we find that the significant human capital determinants are an entrepreneur's intuition and propensity for innovating activities. In terms of organisational capital determinants, we reveal that the significant variables are an efficient organisational structure and the use of external indicators to improve entrepreneurial performance.